The Effectiveness of Teaching with Model-‎Eliciting Activities (MEAs) in Developing ‎Mathematical Thinking among Students in the ‎Tenth-grade in the Sultanate of Oman - Al-Mukhini, Wedad; Al-Shannaq, Mamoon (Jordan Journal of Educational Sciences, 2024)
The study aimed to investigate the effectiveness of teaching with Model-Eliciting activities (MEAs) in developing mathematical thinking among tenth-grade students in the Sultanate of Oman. A quasi-experimental design was used. The sample of the study consisted of 150 female and male students. It was divided equally into two groups: an experimental group who were taught according to the Model-Eliciting Activities (MEAs); and a control group who were taught using the conventional method. To achieve the aims of the study, the study instrument was prepared, the mathematical thinking skills test, which consists of 13 different questions. The validity and reliability of the instrument were verified. The results showed statistically significant differences at (α=.05) in the mathematical thinking skills test, in favor of the experimental group. The results also showed that there were statistically significant differences at the level of (α =.05) in the mathematical thinking skills test between males and females, in favor of females. The results also showed that there were no statistically significant differences between the average scores of students in the two groups of the study in mathematical thinking skills attributed to the interaction between group and gender. In light of these results, the study provided several recommendations, including utilizing the educational model based on eliciting activities (MEAs)presented by the study, as well as the mechanisms for employing it in mathematics instruction